RETRACTED: Design of a dual axis solar tracking system with strong wind protection system - Ergashev Sirozhiddin; Oshchepkova Elvira (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001